Rational design and fabrication of sulfur-doped porous graphene with enhanced performance as a counter electrode in dye-sensitized solar cells. Issue 5 (13th January 2017) - Meng, Xiangtong; Yu, Chang; Song, Xuedan; Liu, Zhiqiang; Lu, Bing; Hao, Ce; Qiu, Jieshan
Abstract : Sulfur-doped porous graphene materials were engineered, which experimentally and theoretically exhibit excellent electrocatalytic activity toward I3 − reduction and great potential toward Pt replacement for DSSCs. Abstract : Exploring cost-effective counter electrodes (CEs) with high electrocatalytic activity and excellent electrochemical stability is one of concerned issues for practicable applications of dye-sensitized solar cells (DSSCs). Graphene (G), featuring unique and intriguing physicochemical properties, has emerged as one of the most promising candidates. Nevertheless, the relationships between the electrochemical activity and the intrinsic structure of G need to be further understood. Herein, we report a facile yet effective strategy for engineering sulfur-doped porous graphene (SPG) using sulfur powder as the sulfur source and pore-forming agent. The as-made SPG as the CE for DSSCs achieves a high power conversion efficiency of 8.67%, which is superior to Pt (7.88%), and robust electrochemical stability. The influence of annealing temperature on SPG is analyzed, and SPG prepared at 900 °C shows the best photovoltaic and electrochemical performance. Both experimental and theoretical efforts first elucidate that highly exposed rich edge sites and interconnected porous channels, as well as low ionization energy derived from sulfur species within the G matrix play vital roles in enhanced reaction kinetics and triiodide reduction activity. The present work will inspire the construction of porous graphene with surface-enriched active sites and interconnected networks for advanced energy applications.